Sawdust-derived Biochar: characterization and Co2 adsorption/desorption study - Wan Ab. Karim Ghani, Wan Azlina; Da Silva, Gabriel (Asian Network for Scientific Information, 2014)
Sawdust-derived Biochars (SDB) was prepared in a stainless steel fixed bed pyrolyser of 43 mm height and 60 mm internal diameter at four different operating temperatures ranging from 450 to 850°C. SDB physico-chemical characterization such as surface area, functional groups and surface morphology were analyzed by N2 physisorption, Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM), respectively. SDBs to have a surface area between 10 to 200 m2g-1 and FTIR revealed an aromatic functional group about 866 cm-1 in most biochar samples. The experimental data shows that the biochars can absorb around 5% water by mass (hydrophilic) at lower temperatures (<550°C) and FTIR results indicated that lignin is not converted into a hydrophobic polycyclic aromatic hydrocarbon (PAH) matrix. While, at higher temperature (>650°C), biochars is thermally stable and became hydrophobic due to the presence of aromatic compounds. The SDB is used for the adsorption of carbon dioxide (CO2) and its can be apply for the removal of CO2 from environment.